Canal operations planner. I: maximizing delivery performance ratio - Anwar, Arif A.; Bhatti, Muhammad Tousif; Vries, T.T. de (American Society of Civil Engineers, 2016)
A key operational objective for the management of the Indus Basin Irrigation System of Pakistan is the distribution of water among tertiary canals in a transparent and equitable manner. Decisions on canal operations are disseminated as a Canal Operation Plan, or a Rotational Program, for each crop season for every canal system. The current practice for developing these plans is qualitative based on heuristics that have remain unchanged since the early development of this vast irrigation system. This paper uses operations research tools to develop a Canal Operations Planner. Allocation cost is defined as a function of the delivery performance ratio and maximizing this function. The performance of the modules is evaluated using spillage and the Gini index as a measure of equity. Two models, namely; linear programme-delivery performance ratio (LP-DPR) and non linear programme-delivery performance ratio (NLP-DPR) are presented and the results are compared to performance under current canal planning and operational practice. Both models improve the equity when compared to existing operations. The NLP-DPR model outperforms the LP-DPR both on equity and minimizing spillage.